Nivel de conocimiento de los estudiantes de sexto a décimo ciclo de la carrera de Odontología de la Universidad Nacional de Loja sobre el uso del flúor - Macas Jumbo, María Fernanda (2019)
Scientific evidence on the benefits and harms of the use of fluorides has been responsible for a major change in dental practice, it is extremely important and fundamental the knowledge about the management of fluorides and administration protocols by professionals and students of Dentistry. The present investigation aims to determine the level of knowledge of students from sixth to the tenth cycle of the career of Dentistry of the National University of Loja about the use of fluorine; it is a descriptive study, a questionnaire of 20 dichotomous questions was applied to a non-probabilistic sample of 126 students selected for convenience; an encoding of each of the items of the questionnaire was developed and the cut-off points were calculated to establish a scale with ranges, Considering for the handling of fluorides: 16 to 20 (low), 21 to 25 (medium), greater than 25 (high); and for fluoride administration protocols: 5 to 6 (low), 7 to 8 (medium) and greater than 8 (high). It was obtained as results that: students are at a high level of knowledge with 81% regarding the management of fluorides in odontopediatrics patients; likewise the high level of knowledge with 70.60% in reference to the fluorine administration protocols. In conclusion, the majority of students who perform pre-professional practices in the career of dentistry have a high level of knowledge in both the management and administration of fluorine. Keywords: benefits, fluorides, protocols, toxicity.